Wildfire Smoke Effects on Lake‐Habitat Specific Metabolism: Toward a Conceptual Understanding. Issue 7 (5th April 2022) - Scordo, Facundo; Sadro, Steven; Culpepper, Joshua; Seitz, Carina; Chandra, Sudeep
Abstract: The impacts of wildfire smoke on lake habitats remains unclear. We determined the metabolic response to smoke in the epi‐pelagic and two littoral habitats in Castle Lake, California. We compared light regime, gross primary production, ecosystem respiration, and net ecosystem production in years with and without smoke. During the smoke period incident ultraviolet‐B (UV‐B) radiation and photosynthetically active radiation (PAR) decreased by 53% and 28%, respectively, while the water column extinction coefficient of UV‐B and PAR increased by 20% and 18% respectively. Epi‐pelagic productivity increased during smoke cover because of decreased solar inputs. PAR values remained sufficient to saturate productivity, suggesting observed differences were primarily the result of changes in UV‐B. Littoral‐benthic productivity did not change, possibly reflecting adaptation to high‐intensity UV‐B light in these habitats. Our results highlight the importance of understanding how prolonged wildfire smoke alters the amount of energy produced from specific habitats in lakes. Plain Language Summary: Large wildfires are increasing worldwide, but the impacts of wildfire smoke on lakes are unknown. We determined how photosynthetic activity and organism's respiration respond to smoke in the offshore and nearshore habitats in a mountain lake. Smoke limited the damage to algae caused by ultraviolet‐B radiation, resulting in increased offshore photosynthesis. Photosynthesis in the nearshore habitat did not change during smoke cover, possibly because organisms in shallow habitats have adapted to the higher intensity of damaging ultraviolet‐B radiation. Our results highlight the importance of understanding how prolonged smoke conditions can alter lakes' energy flows and food webs. Key Points: Wildfire smoke reduced ultraviolet‐B and photosynthetically active radiation Lake habitats respond differently to changes in light from smoke, pelagic primary production increased with no change to littoral metabolism Smoke alters energy flows with implications for food web structure in lakes